A case of progressive aphasia without dementia: "temporal" Pick's disease?. Issue 1 (January 1990) - Scheltens, P; Hazenberg, G J; Lindeboom, J; Valk, J; Wolters, E C
Abstract : We report a patient who suffered from progressive aphasia for nine years, before developing mild behavioural disturbances. Sequential computed tomography (CT) scanning and magnetic resonance (MRI) imaging showed progressive bilateral temporal atrophy. The case is thought to be a temporal form of Pick's disease, in which isolated progressive aphasia was the only symptom over many years.